Nutritional value and potential chemical food safety hazards of selected Polish sausages as influenced by their traditionality. (May 2018) - Halagarda, Michał; Kędzior, Władysław; Pyrzyńska, Ewa
Abstract: Traditional food products have been regaining consumer interest worldwide. The aim of the study was to investigate the differences in nutritional value of traditional and conventional Polish sausages and to determine potential chemical hazards connected with these products. The research material consisted of 5 varieties of registered traditional sausages and 4 varieties of conventional sausages. The nutritional value was identified based on selected indicators: protein, fat, NaCl, total ash, water, Feder's number, Ca, Fe, Mg, K, Zn, Cr, Cu; whereas the chemical food safety - based on: nitrates and nitrites, total and added phosphorus, Cd, Pb. The results of this study show that traditional sausages have higher content of protein, zinc, magnesium and potassium as well as lower concentrations of calcium, water and total ash, plus lower water to protein ratio in comparison to conventional counterparts. Polyphosphates are not used in the production of traditional sausages and the amounts of added nitrites are at low levels. Highlights: The chemical safety and nutritional value of Polish sausages were tested. Traditional and conventional sausages were examined. The PCA was used to illustrate the differences between the tested groups of sausages. The highest nutritional value of traditional sausages was confirmed.